PENGARUH PENERAPAN MODEL PBL BERBANTUAN MEDIA GOOGLE CLASSROOM TERHADAP HOTS, MOTIVASI DAN MINAT PESERTA DIDIK - Nurul Komariah; Mujasam M.; Irfan Yusuf; Sri Wahyu Widyaningsih (LP4MK STKIP PGRI Lubuklinggau, 2019)
TThe study has bee carried out with a view to estamblishing an aplication of the opposing problem based learning model help the google classroom on the HOT, motivation and interest student yapis manokwari high school. The focus treatment is from yhe realm C4, C5 and C6. Researdch methods pre eksperimental designwith researdch desigh is the one group pretes-posttest design.the subjek in this study is a leaner’s class XII IPA high school of Yapis Manokwari 21 person. Results pretest and posttest in normal distribution and homogenized analysis, this hypotesis was tested using the wilcoxson test for its significance α = 0,05. value results is sig 2 tailed is 0,00 which is less than an significance 0,05 so his hypothetical decision is H0 is bounce or HA be accepted, thus there is influence from aplication of the problem based learning model help the google classroom on the higher order thingking skill (HOTS), as well as enaugh grades for HOTS in the kategory, motivation and interest student yapis manokwari high school. Spacing data analyzed using winstep, where person measure 0,58 ˃ 0,00 for motivation and 0,08 ˃ 0,00 for interest. Generally learners have good motivation and interest in learning.